Motility in Echinosphaerium nucleofilum. II. Cytoplasmic contractility and its molecular basis (The Rockefeller University Press, 1975)
Echinosphaerium nucleofilum exhibits at least three kinds of movement: locomotion by the bending and shortening of its many axopodia, feeding by means of food-cup pseudopodia formed from its cortical cytoplasm, and saltatory motion of cytoplasmic particles, especially in the cortex and axopodia. Since previously presented evidence indicated that the microtubular axoneme is not essential for particle motion, the cytoplasm was investigated for the possible existence of contractile behavior and for the possible presence of linear elements other than microtubules. Cytoplasm can be isolated in physiological media in which rigor, relaxation, and contraction can be induced, as in muscle, by manipulating the concentrations of calcium ions and magnesium-adenosine triphosphate. Contraction is initiated by calcium ions at concentrations above 2.4 times 10-minus 7 M. The rigor-to-relaxation transition occurs at subthreshold calcium concentrations on the addition of 10-minus 3 M ATP. Negatively stained preparations of isolated cytoplasm show two types of filaments: thin filaments identified as cytoplasmic actin by virtue of their binding heavy meromyosin from striated muscle in characteristic arrowhead arrays, and thicker filaments which do not strictly resemble myosin aggregates from muscle or amoeba but could conceivably by myosin aggregated in an unfamiliar form.